Biharmonic General Helices in 3-Dimensional Finsler Manifold - Yılmaz, Münevver Yıldırım (My University, 2017)
In the present paper, we study on the 3- dimensional Finsler manifold and obtain some characterizations for helices of this space.
Keywords: Matematik; Fizik; Matematik